Determining the impact of a magnetoelectric generator on the operation of a local distribution network - Chumack, Vadim; Katsadze, Teimuraz; Bazenov, Volodymyr; Kovalenko, Mykhailo; Geraskin, Olexandr (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is electromagnetic processes in a magnetoelectric generator with a capacity of 15 kW, operating in a local distribution network. Using a magnetoelectric generator in parallel with a local distribution network makes it possible to improve the reliability and efficiency of such a system. The advantages and disadvantages of the options for regulating the load characteristic of magnetoelectric generators for low-power energy complexes, for example, mini-hydroelectric power plants, have been analyzed. A system for regulating the output voltage of magnetoelectric generators with a capacity of up to 15 kW has been proposed and implemented using known and available semiconductor circuit solutions. Several options for connecting individual coils of the generator armature winding with excitation from permanent magnets were investigated; the external characteristics corresponding to these options are shown. It is shown that when connecting the generator armature winding coils in parallel groups, it is possible to obtain the least distortion of the output voltage. At a load of 0.5–1.1 Іr, the rigidity of the characteristic allows it to meet the regulatory requirements of –10 %...+5 % of the rated voltage. Analysis of the operation of a magnetoelectric generator when controlled by triacs at a given voltage range and when operating on variable active resistance without the use of semiconductor regulators has been carried out. The forms of the generator output voltage on real samples with different control schemes are presented. The possibility of connecting an autonomous generator to a local distribution network in the absence of load for the purpose of implementation on the electricity market has been investigated. The form of the output voltage with the least distortion acceptable for the distribution network according to the standards for the quality of electric energy has been selected